DISPARITAS PUTUSAN HAKIM TERHADAP TINDAK PIDANA NARKOTIKA DI WILAYAH HUKUM PENGADILAN NEGERI RANTAUPRAPAT - Haerul Mustofa; Henky Chandra (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2024)
Different decisions result in arguments about the same customer against two different defendants with different charges. This study is basically descriptive normative law. The research results show that: Both assessments cited as case studies are based on inequality theory. The actual decision is heard in court and handled in a certain way By law. However, these results are not in accordance with the sense of justice that emerged in 2000. general; It would be better for the judge who hears this case to look at the actual legal facts in more depth to find the real truth of a problem. I have tried. The factors causing disparities in judges' decisions regarding drug offense cases covered in this research are: a) There are legal reasons for several interpretations of Articles 112 and 127 of the Narcotics Law. b) law enforcement factors; The judge has the discretion to exercise the power of discovery. Truth is not actually used by the judge in making decisions. c) legal and cultural factors; There is a culture of bribery and conciliation, processing requests and decisions of light punishment. Stakeholders must work together to decriminalize diversion by drug users regarding administrative procedures and medical services